England's Stewardship : The Substance of a Sermon Preached on the Fast-Day, in Trinity Church, Tunbridge Wells - Hoare, Edward, 1812-1894 (Salt Lake City, UT : Project Gutenberg, 2016)
"England's Stewardship" by Edward Hoare is a religious discourse that presents a sermon delivered on a fast-day at Trinity Church, Tunbridge Wells, likely in the mid-19th century. This book, grounded in Christian thought, examines England's moral responsibilities as a colonial power, particularly in relation to India during a time of crisis marked by suffering and strife. The author argues for a reflective stewardship where the light of Christianity must be shared with the nations under English governance, emphasizing the ethical implications of colonial actions. In the sermon, Hoare calls attention to the heavy burden of stewardship that England shoulders over its colonial territories, specifically India. He discusses the juxtaposition of England's wealth and influence against the suffering of the Indian population, encouraging a national introspection on the moral consequences of colonialism. The text critiques the government's actions, particularly regarding the opium trade and religious neutrality, while highlighting both the progress made and the failures of the Church in spreading Christian teachings. Through vivid descriptions and appeals to empathy, the author compels readers to acknowledge their collective responsibilities. Ultimately, Hoare's message is a plea for a more noble application of England's stewardship by aligning actions with Christian principles. (This is an automatically generated summary.)
Release date is 2016-08-08
Transcribed from the 1857 Thomas Hatchard edition by David Price
Keywords: Church of England -- Sermons; India -- History -- British occupation, 1765-1947; Sermons, English -- 19th century